From the Pulpit to the Feed: The Transformation of Da'wah Rhetoric and Its Relevance to the Formation of Millennial Islamic Identity - Muhammad Deni Azhari (Social Science Academic, 2026)
The proliferation of social media platforms such as Instagram, YouTube, and TikTok has fundamentally altered the way Islamic preaching (da'wah) is composed, delivered, and consumed in Indonesia. What was once bound to the linear, face-to-face structure of the khutbah (sermon) delivered from the pulpit has been reconfigured into short, algorithmically circulated, and highly visual "content." This article examines how this shift in rhetorical form relates to the construction of Islamic identity among the millennial generation. Using a qualitative library research design combined with critical discourse analysis of existing scholarship, the study traces the transformation of da'wah rhetoric across three dimensions: structural (from the five classical canons of rhetoric to the algorithmic logic of platforms), authoritative (from scholarly lineage to affective visibility), and communal (from congregational presence to networked, parasocial belonging). The findings indicate that classical rhetorical appeals identified by Aristotle—ethos, pathos, and logos—remain conceptually relevant but are reconfigured by the affordances of digital media: ethos is now built through visual branding and follower metrics rather than institutional pedigree; pathos is intensified through short-form emotional storytelling; and logos is compressed into quotable, meme-able fragments of religious argument. This transformation contributes to a hybrid millennial Islamic identity that is simultaneously pious and performative, communal and individualized, orthodox in content yet informal in style. The article concludes that the transformation from khutbah to content does not eliminate rhetorical persuasion in da'wah but repackages it, with significant implications for religious authority, media literacy, and the pedagogy of contemporary Islamic communication.